2015
DOI: 10.1371/journal.pone.0141138
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of Genes Related to Growth and Lipid Deposition from Transcriptome Profiles of Pig Muscle Tissue

Abstract: Transcriptome profiles established using high-throughput sequencing can be effectively used for screening genome-wide differentially expressed genes (DEGs). RNA sequences (from RNA-seq) and microRNA sequences (from miRNA-seq) from the tissues of longissimus dorsi muscle of two indigenous Chinese pig breeds (Diannan Small-ear pig [DSP] and Tibetan pig [TP]) and two introduced pig breeds (Landrace [LL] and Yorkshire [YY]) were examined using HiSeq 2000 to identify and compare the differential expression of funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
66
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 60 publications
5
66
0
Order By: Relevance
“…In our previous study, two indigenous Chinese pig breeds (DSP and TP) had significantly lower body weights and higher intramuscular fat (IMF) than those of two introduced pig breeds (LL and YY)25. In the present study, we found that the diameter of muscle fascicles was markedly smaller in TP and DSP than in LL and YY, indicating differential muscle development between Chinese and introduced pig breeds.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…In our previous study, two indigenous Chinese pig breeds (DSP and TP) had significantly lower body weights and higher intramuscular fat (IMF) than those of two introduced pig breeds (LL and YY)25. In the present study, we found that the diameter of muscle fascicles was markedly smaller in TP and DSP than in LL and YY, indicating differential muscle development between Chinese and introduced pig breeds.…”
Section: Discussionsupporting
confidence: 44%
“…In our previous study, we identified genes related to growth and lipid deposition from the transcriptome profiles of LD muscles of pigs25. In the present study, we performed iTRAQ-based quantitative proteome analysis of the Chinese indigenous (TP and DSP) and introduced (YY and LL) pig breeds to identify functional proteins associated with muscle growth and lipid deposition pathways.…”
mentioning
confidence: 99%
“…Adipogenesis of intramuscular preadipocytes has been determined via genetics (4), epigenetics, and transcriptomic mechanisms (5,6). Epigenetic imprinting through DNA methylation (7)(8)(9), microRNAs (10,11), and noncoding RNAs (12) play important roles in preadipocytes adipogenesis.…”
mentioning
confidence: 99%
“…However, this process could be reversed by fat mass and obesity-associated protein (FTO) (17) or AlkBH5 (18). In addition, the YTH domain family (YTHDF) proteins YTHDF1-3 (19)(20)(21) and YTHDC1 (22) are believed to modulate m 6 A residues on mRNAs, thus regulating various aspects of RNA metabolism such as mRNA transcription (20,23), splicing (22), and stability (19). Previous studies reported that m 6 A modification down-regulates adipogenesis in porcine adipocytes (24), and it may affect adipogenesis by regulating alternative RNA splicing (25).…”
mentioning
confidence: 99%
“…A large number of candidate genes between the psoas and the longissimus dorsi (LD) were obtained by cDNA microarray chip of porcine skeletal muscle18. A total of 315 differentially expressed genes (DEGs), including 240 genes annotated to the DAVID database, were obtained by comparing the LD sequencing results of the Chinese pig and imported pig19. In our research group, a significant number of DEGs associated with labor onset have been obtained via comparison of sequencing data from a shorter gestation period and a normal gestation period20.…”
mentioning
confidence: 99%